2021
DOI: 10.1136/neurintsurg-2021-017416
|View full text |Cite
|
Sign up to set email alerts
|

CLinical Assessment of WEB device in Ruptured aneurYSms (CLARYS): results of 1-month and 1-year assessment of rebleeding protection and clinical safety in a multicenter study

Abstract: BackgroundThe primary goal of the CLARYS study is to assess the protection against rebleeding when treating ruptured bifurcation aneurysms with the Woven EndoBridge (WEB) device.MethodsThe CLARYS study is a prospective, multicenter study conducted in 13 European centers. Patients with ruptured bifurcation aneurysms were consecutively included between February 2016 and September 2017. The primary endpoint was defined as the rebleeding rate of the target aneurysm treated with the WEB within 30 days postprocedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 28 publications
1
38
1
Order By: Relevance
“…In accordance with recent publications,2 25 the use of the WEB in a ruptured aneurysm or in association with a stent was feasible and effective, without significantly influencing the rate of angiographic occlusion. Also, we noted that the use of antiplatelet therapy after embolization did not significantly influence the outcome.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In accordance with recent publications,2 25 the use of the WEB in a ruptured aneurysm or in association with a stent was feasible and effective, without significantly influencing the rate of angiographic occlusion. Also, we noted that the use of antiplatelet therapy after embolization did not significantly influence the outcome.…”
Section: Discussionsupporting
confidence: 79%
“…Since then indications for WEB have been widened—for example, to ruptured aneurysms, side-wall aneurysms. or in association with other devices 2–4…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we show overall mortality to be higher than that reported by others (range between 1% and 10%) [ 7 , 20 ]. Particularly, Pierot et al in 2021 reported a 6.3% of global mortality at 3 years, with 1 death related to the procedure and 4 deaths unrelated to the procedure.…”
Section: Discussioncontrasting
confidence: 56%
“…The ability of WEB to prevent rebleeding has been investigated by the CLARYS study [ 7 ]. Specifically, this trial included 56 ruptured WNBAs, showing a zero rate of rebleeding at 1 month and 1 year, indicating that an implanted WEB device is highly effective in preventing early and mid-late rebleeding.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] The CLinical Assessment of WEB device in Ruptured aneu-rYSms (CLARYS) study is a post-market, open label, nonrandomized, prospective study in Europe. The interim results have already been analyzed and published, 18 showing that the endovascular treatment of ruptured bifurcation aneurysms with the WEB is safe and effective, as evidenced by a zero rebleeding rate and a low complication rate observed at 1-month follow-up. The present analyses focus on safety and anatomical results at 1 year.…”
Section: Hemorrhagic Strokementioning
confidence: 99%